Clinical Profile of Patients With Dry Beriberi Attending At Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Dry beriberi is a manifestation of thiamine (Vitamin B1) deficiency that primarily affects the peripheral nervous system. It can occur independently or with other forms of beriberi, such as Wernick’s encephalopathy, Korsakoff Psychosis, wet beriberi etc. To describe the socio-demographic profile of dry beriberi patients and the common clinical patterns of dry beriberi presentation.Materials and methods: This descriptive observational study was conducted among adult patients with possible dry beriberi admitted into the Neurology Department of Chittagong Medical College Hospital (CMCH) from May 2018 to November 2018.  A total of 55 patients were recruited by consecutive sampling method. Data collected by structured questionnaire was analyzed for descriptive statistics by using SPSS Version 23.  Results: The mean age of the subjects was 31.1±12.0 years (18-65 years). There was female predominance with a male-to-female ratio of 1:2.3. About half of them had educational qualifications below SSC level and lived in rural areas. Majority (58.2%) of them had a monthly family income of 10,000-20,000 taka. All patients consumed polished rice ‘Atop’. All of them was hed rice > 3 times before cooking and none of the patients was purely vegetarian. Among 55 patients, 50 (92%) patients consumed tea, 12(21.8%) persons ate betel nuts immediately after the major meal and 2(1.1%) ate fermented fish occasionally as part of their typical diet. The mean BMI was 24.2 ± 3.1 SD.  Many of them (67.3%) had clinical evidence of anaemia. The most common presenting symptoms were limb weakness (100%). Other presenting features were leg swelling (98.2%), sensory impairment (Pain, tingling and numbness in limb) (90.9%) anorexia and nausea (50.9) muscle cramps (30.9%) etc.Conclusion: Dry beriberi is a neglected but serious condition that can lead to significant neurological impairment if left untreated. Prompt recognition and appropriate management with thiamine supplementation are crucial for preventing long-term complications.JCMCTA 2024 ; 35 (2) : 67-71